Degenerate nonlinear boundary-value problems - Boichuk О. A.; Shehda, L. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish necessary and sufficient conditions for the existence of solutions of weakly nonlinear degenerate boundary-value problems for systems of ordinary differential equations with a Noetherian operator in the linear part. We propose a convergent iterative procedure for finding solutions and establish the relationship between necessary and sufficient conditions.